2011
DOI: 10.4103/0019-5154.84765
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of skin tags in relation to obesity, type 2 diabetis mellitus, age, and sex

Abstract: Background:Skin tags (STs) have been investigated as a marker of type 2 diabetes mellitus (DM), yet the relation of STs to obesity is still a matter of controversy.Aim:The aim of the study is to explore the relation of number, size and color of STs to obesity, diabetes, sex and age in one study.Methods:The study included 245 nondiabetic (123 males and 122 females) and 276 diabetic (122 males and 154 females) subjects. We recorded age, sex, body mass index (BMI), relevant habits, STs color, size, and number in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
3
19
0
2
Order By: Relevance
“…While in study done by Omar et. Al 5 , the mean number of medium size skin tags was significantly higher in diabetic participants than non diabetics (p = 0.003). Skin tags are related to obesity, 9 and a hormonal mechanism has been suggested in obese females especially those with upper body obesity, where there is increased peripheral aromatization of androgens to estrogen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While in study done by Omar et. Al 5 , the mean number of medium size skin tags was significantly higher in diabetic participants than non diabetics (p = 0.003). Skin tags are related to obesity, 9 and a hormonal mechanism has been suggested in obese females especially those with upper body obesity, where there is increased peripheral aromatization of androgens to estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The study done by Omar et al showed that the prevalence of Skin tags were more among diabetic patients. 5 Similarly, study of Demir et al 7 showed that patients with skin tags were found to have overt DM. They found diabetes in 73.3% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Część badaczy uważa, że mogą być one użytecznym objawem wskazującym na zwiększone ryzyko rozwoju miażdżycy [7,[9][10][11]. W pracy Shah i wsp.…”
unclassified
“…Podobnie jak w poprzednim badaniu frakcja HDL cholesterolu w surowicy była obniżona, a pacjenci mieli wyższe skurczowe i rozkurczowe ciśnienie krwi [13]. W badaniu przeprowadzonym przez Demir i Demir zdiagnozowano cukrzycę aż u 73,3% pacjentów mających włókniaki [14], natomiast El Safoury i Ibrahim stwierdzili związek ich liczby przede wszystkim z otyłością i wiekiem, niezależnie od płci [10]. Potwierdza to badanie Gómez i wsp.…”
unclassified